2012
DOI: 10.7314/apjcp.2012.13.9.4689
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in PDCD6 and Susceptibility to Lung Cancer

Abstract: Lung cancer is the most common type of cancer and one of the leading causes of death in the world. Genetic factors play an important role in its development. PDCD6, the encoding gene for programmed cell death protein 6, may function as a tumor suppressor gene. Non-small cell lung cancer (NSCLC) contributes about 80% to newly histologically diagnosed lung cancer patients. To explore the relationship between PDCD6 and NSCLC, we examined two single nucleotide polymorphisms(rs3756712 G/T andrs4957014 G/T, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…59,60 One single nucleotide polymorphism rs4957014 in the intron region of the PDCD6 gene significantly increased NSCLC risk. 61 SiRNA-mediated knockdown of CKS1B resulted in a significant decrease in lung cancer cell proliferation, invasion, and migration and sensitized the response of lung cancer cell lines to cisplatin and paclitaxel. Cyclin-dependent kinase CKS1B regulates lung cancer progression and chemoresistance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…59,60 One single nucleotide polymorphism rs4957014 in the intron region of the PDCD6 gene significantly increased NSCLC risk. 61 SiRNA-mediated knockdown of CKS1B resulted in a significant decrease in lung cancer cell proliferation, invasion, and migration and sensitized the response of lung cancer cell lines to cisplatin and paclitaxel. Cyclin-dependent kinase CKS1B regulates lung cancer progression and chemoresistance.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of lung cancer demonstrated that PDCD6 overexpression was indicative of poor prognosis for patients with early stage NSCLC or LUAD . One single nucleotide polymorphism rs4957014 in the intron region of the PDCD6 gene significantly increased NSCLC risk . SiRNA‐mediated knockdown of CKS1B resulted in a significant decrease in lung cancer cell proliferation, invasion, and migration and sensitized the response of lung cancer cell lines to cisplatin and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [ 42 , 45 , 44 , 9 ] reported the association between rs3756712 and rs4957014 polymorphisms and cancer. As shown in Figure 3 and Table 2 , the results showed that PDCD6 rs3756712 T>G polymorphism was significantly associated with decreased risk of cancer under codominant (OR = 0.82, 95%CI = 0.70–0.96, p = 0.01, TG vs TT; OR = 0.53, 95%CI = 0.39–0.72, p < 0.0001, GG vs TT), dominant (OR = 0.76, 95%CI = 0.66–0.89, p = 0.0004, TG+GG vs TT), recessive (OR = 0.57, 95%CI = 0.43–0.78, p = 0.0003, GG vs TT+TG), and allele (OR = 0.76, 95%CI = 0.67–0.86, p <0.00001, G vs T) genetic model.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies inspecting the association between PDCD6 gene polymorphisms and cancer indicated inconclusive and contradictory results [ 9 , 45 , 44 , 42 ]. Hence, we have performed a meta-analysis on all the published case-control studies to evaluate the association of PDCD6 rs3756712 T>G and rs4957014 T>G gene polymorphisms with the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PDCD6 is a calcium-binding modulator associated with cell proliferation and death (38). Numerous studies have revealed that PDCD6 is associated with tumors; however, the underlying mechanism remains unclear (39)(40)(41)(42). Furthermore, one study demonstrated that overexpression of PDCD6 suppressed angiogenesis in vitro via the phosphatidylinositol 3-kinase/protein kinase mTOR/ribosomal protein S6 kinase B1 pathway (43).…”
Section: Discussionmentioning
confidence: 99%